The Assessment: Games and Coordination. - Myatt, D; Shin, H; Wallace, C (2002)
Coordination problems arise in a multitude of economic interactions. Recent advances in the field of game theory have shed new light on these problems and the ways in which they might be analysed. This issue of the Oxford Review of Economic Policy first examines some of the theoretical dimensions to this literature, as well as some empirical and experimental insights. It goes on to apply some of these ideas to a number of important policy areas, including macroeconomic policy coordination, public good provision, and problems of political coordination.